Marine monitoring in transition: On the verge of technological revolution? - Korpinen, Samuli; Kahlert, Maria; Kuosa, Harri; Mack, Leoni; Meissner, Kristian; Pitkänen, Heikki; Pyhälahti, Timo; Uusitalo, Laura (Frontiers in Marine Science, 2022)
Efforts to renew marine ecosystem monitoring to include advanced technology and cost-effective methods have been repeatedly called for. The current environmental legislation in European Union (EU) requires also ecosystem monitoring beyond the scope of conventional methods and sampling strategies. Despite several studies showing the benefits of new methods, the progress to adopt the methods in national monitoring programmes under legal requirements has been slow. In this study, we have reviewed the current use of a set of methods in marine monitoring programmes under the EU marine strategy framework directive (MSFD), which calls for a holistic view of the marine environment and thus requires tens of monitoring parameters by different methods. Here we assess how widely the new methods are being adopted in the EU member states implementing the MSFD. Our results show a relatively high adoption rate for certain methods, while others are widely ignored. We compare the results also with the monitoring strategies of the four regional sea conventions. We argue that the adoption of methods in European and regional programmes may positively influence the national use of new methods.